UJI TOKSISITAS EKSTRAK ETANOL DAUN SIRIH HUTAN (Piper aduncum L.) - Sri Wahyuni; Erwin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Forest betel (Piper aduncum L.) is one of the largest general in tropical regions, with more than 1000 species estimated within the Piperaceae family. In Indonesia, it is widely distributed across Papua, where its habitat occupies nearly a significant portion of the secondary forest areas. Traditionally, the leaves of forest betel are used as a remedy for canker sores, leucorrhea, mouthwash, internal wounds, to stop vomiting, reduce nausea, promote digestion, act as an antiseptic, and kill bacteria, fungi, and viruses. The objective of this research is to identify the secondary metabolites present in the leaves of forest betel (Piper aduncum L.), analyze the toxicity level, and assess the antioxidant activity of the ethanol extract of forest betel leaves (Piper aduncum L.). The methods employed in this study include extraction, phytochemical screening, toxicity testing using the Brine Shrimp Lethality Test (BSLT), and antioxidant activity testing using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The results of the phytochemical screening test showed that the ethanol extract of forest betel leaves (Piper aduncum L.) contains alkaloid, triterpenoid, phenolic, flavonoid, and quinone compounds. Based on the toxicity test, the ethanol extract of forest betel leaves (Piper aduncum L.) exhibited a toxicity level of 6.12915 x 10-13 ppm, categorized as toxic (<1000 ppm), suggesting that the ethanol extract has bioactivity as it is toxic to Artemia salina L. larvae. Keywords : Antioxidant, Toxicity, Forest Betel Leaves, Phytochemistry, Secondary Metabolites